Candy of Cannabis sativa L.- A traditional intoxicant in Udaipur, Rajasthan - Vartika Jain (Journal of Traditional and Folk Practices (JTFP), 2016)
Plants and plant products are part of many socio-cultural events. An ethnobotanical survey to famous Jawar Mata fair at Jawar village, Udaipur, Rajasthan has revealed selling of candies made up from leaves of Cannabis sativa L. for recreational purpose. Although illegal, selling of Cannabis in this form, acts as a cheap traditional intoxicant as well as a source of income for rural and tribal population of the village.